2018
DOI: 10.1093/ajcn/nqy167
|View full text |Cite|
|
Sign up to set email alerts
|

Differential effects of medium- and long-chain saturated fatty acids on blood lipid profile: a systematic review and meta-analysis

Abstract: The findings of this research demonstrate a differential effect of MCFAs and LCSFAs on HDL cholesterol concentrations. Further investigations are warranted to elucidate the mechanism by which the lipid profile is altered. This trial was registered at www.crd.york.ac.uk/PROSPERO as CRD42017078277.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…A total of 1098 studies were identified, of which 9 met the inclusion criteria ( Figure 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1098 studies were identified, of which 9 met the inclusion criteria ( Figure 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…MCFA-rich diets can increase high-density lipoprotein levels in humans compared to saturated LCFA-rich diets (Panth et al, 2018), with mixed reports on low-density lipoprotein (LDL) levels (Marten et al, 2005). If MCFAs exist in LDL, then they could also present at macrophages as oxidized LDL (oxLDL) during atherogenesis.…”
Section: Lipoprotein Transportmentioning
confidence: 99%
“…SCFAs are produced by the gut microbiome via fermentation of dietary fibers and are distributed across the body through the bloodstream. SCFAs are utilized by the body to provide energy or as signaling molecules ( 81 , 82 ). SCFAs inhibit histone deacetylases (HDACs) and promote anti-inflammatory cell phenotypes (i.e., neutrophils) that maintain homeostasis, and suppress nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and tumor necrosis factor-α (TNF-α) production ( 80 , 83 , 84 ).…”
Section: Lung Microbiome and Asthmamentioning
confidence: 99%